2017
DOI: 10.19044/esj.2017.v13n23p377
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Socio-Economic Characteristics and Utilization of Healthcare Facilities in Owo Local Government Area of Ondo State, Nigeria

Abstract: This paper examines the socio-economic characteristics of residents and their utilization of available healthcare facilities in Owo local government area of Ondo State, Nigeria. The data utilized in the paper draws on systematic sampling of 368 health consumers in the study area. Findings revealed that socio-economic characteristics play a significant role in determining the frequency of visits to healthcare facilities, this is substantiated with the chi-square test result that revealed a significant relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…Furthermore, our findings of other sociodemographic distribution of respondents by marital status, religion, education, occupation, and average family income were consistent with the findings of the report of the integrated households survey in Ondo state as reported by previous authors [20][21][22][23].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our findings of other sociodemographic distribution of respondents by marital status, religion, education, occupation, and average family income were consistent with the findings of the report of the integrated households survey in Ondo state as reported by previous authors [20][21][22][23].…”
Section: Discussionsupporting
confidence: 92%
“…The implication of this is that the majority of respondents can only afford to utilize public healthcare facilities. This concurs with Olugbamila and Adeyinka (2017) findings that human health is vital to economic activity. The analysis revealed that five (5) out of the eight (8) characteristics are linked to health services accessibility and utilization.…”
Section: Discussionsupporting
confidence: 91%
“…Generally, it can be inferred that a large number of respondents are younger than 46 years old in Benin City. This study shows that 82% of respondents were between the ages of 15-45 years old Olugbamila and Adeyinka, (2017). states that young adults utilise healthcare facilities than other age groups.…”
mentioning
confidence: 70%
See 1 more Smart Citation